A efetivação da assistência social no âmbito das entidades sociais privadas : potencialidades e desafios - Paula, Maria da Glória de (2014)
The object of study in the present dissertation is operationalization of social assistance in the ambit of private social entities around the Partenon area, located in Porto Alegre, Rio Grande do Sul. The aim is to analyze how this public politics is being put in practice together with private social entities, given the goals and actions of the Unified Social Assistance System. The discussion is based on a theoretical background sustained in the following theoretical categories: Social Assistance, Unified Social Assistance System, Social Entities, Social Assistance Services and Social Participation, as well as on empirical data taken from the research conducted during 2012 and 2013. The investigation method used here is the dialectical and historical materialism and the type of study is the descriptive-explanatory qualitative one. The data collection technique chosen was the documentary research and the semi structured interview, which instruments were, respectively, documentary research script and interview script, via the non-probabilistic type of sampling. The study has the participation of workers, users and managers, linked to five entities from the selected area, totaling fourteen subjects. The treatment and examination of data were oriented by the technique of analysis of content. At the end of the process, the research contributed to understand and gather the following results: the social entities from the Partenon area deal with social assistance in a way that it oscillates from being a right and a non-right. They realize that the actions related to such politics are predefined and regulated by the State and suggest changing processes in the entities organizational method since the implementation of the Unified Social Assistance System, with special attention to the networking, the unification of social assistance services and, consequently, the overcoming of assistencialism. Although there is an agreement with the public municipal power, the biggest challenge they face is the scarcity of financial resources, given the complex growing needs and demands from the population who has access to their services, such as survival and acceptance security. Even though, it is possible to identify the development of actions in a planned continuous way, which guarantees quality services. However, some aspects of their practices indicate the need for improvement regarding promotion and fostering of participation and social control. Such aspects relate to the exercise of rights defense, allowing awareness, organization and collective mobilization from the users in the search for political and economic structural changes, both inside and outside the entities.